The biological relevance of potentially toxic metals in freshwater fish - Kovacik, Anton; Helczman, Marek; Tomka, Marian; Jambor, Tomas; Kovacikova, Eva; Arvay, Julius (Frontiers in Physiology, 2025)
Trace elements are essential for a number of physiological functions including oxygen transfer, enzymatic reactions and antioxidant protection of the animal organism. Elevated concentrations outside the physiological optimum, on the other hand, can cause undesirable health complications, disrupt metabolic pathways, reproductive capacity, or oxidative balance. The negative anthropogenic impacts on the environment are alarming and the impacts on the aquatic environment have been increasing disproportionately in recent years. Against this background, all potential threats to biota need to be explained and better understood, the possible risks need to be better informed and understood, and a balance needs to be struck between the fundamental nature and the harmful effects of these metals. This mini-review examines the roles of potentially toxic metals including cobalt (Co), copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo) and zinc (Zn) in fish physiology. This document also elucidates the mechanisms underlying the assessment of regulatory processes, the potential negative consequences of overexposure, the interactions of these metals on fish health, and in the environmental context.